A Study of Pituitary Adenoma Surgery: Transphenoidal Microscopic Versus Endoscopic Endonasal Approach (Bangladesh Journal of Neuroscience, 2015)
Background: Transphenoidal endoscopic approach is minimal invasive surgery in case of pituitary adenoma.Objective : To see the outcome of transphenoidal endoscopic and microscopic approach in case of pituitary tumor.Results : This study showed among the 37 patients, 25 (67.6%) were done by transphenoidal microscopic approach and 12 (32.4%) patients were done by endonasal endoscopic approach. Among the 12 patients 8(66.7%) were male and 4(33.3%) were female. Among the 25, patients 15(60%) were male and 10(40%) were female. It was documented that in 12 patients, 10(83.3%) were macroadenoma and 2(16.7%) were microadenoma. It was evident that among the 25 patient 18(72%) were macroadenoma and 7(28%) were microadenoma. Among 12 patients, 11 (91.7%) had preoperative visual disturbance and 1(8.3%) had normal vision. It was observed that among 25 patients, 23(92%) patients had preoperative visual disturbance and 2 (8%) patients had normal vision. Tumor was totally removed in 9(75%) patients in endoscopic approach and 14(56%) in microscopic approach. Clinically 10(83.3%) patients were improved in endoscopically and 16(64%) patients were improved in microscopic group.Conclusion: It was concluded that endoscopic endonasal approach is better than transphenoidal microscopic approach.Bangladesh Journal of Neuroscience 2015; Vol. 31 (1): 21-29